The Effectiveness of Education Using WhatsApp About the Importance of Pregnancy Checks for Increasing the Knowledge of Pregnant Women in Karangsinom Village, Tirtamulya District, Karawang Regency in 2023 - Puspita, Tita; Rismayanti, Tetin (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Education via whatsapp about the importance of prenatal checks has been proven to increase pregnant women's knowledge. Through this platform, information about the benefits and importance of routine pregnancy checks can be conveyed easily by health workers and pregnant women in access to the WhatsApp application. Purpose of Writing: to find out the Effectiveness of Education Using WhatsApp About the Importance of Pregnancy Checks for Increasing Knowledge of Pregnant Women. Research Methods: Pre-experimental research with the type of one group pre test – post test design by means of a causal relationship by involving one group of subjects. the subject group was observed before the intervention was carried out and then observed after the intervention was carried out. The sampling technique is non-probability sampling with a purposive method. Research Results: This study obtained the results of the Wilcoxon statistical test, which obtained a sig. (0.000) < 0.05, which means there is a difference in knowledge before and after education via whatsapp. It can be concluded that there is Effectiveness of Education with WhatsApp About the Importance of Pregnancy Checks for Increasing Knowledge of Pregnant Women in Karangsinom Village, Tirtamulya District, Karawang Regency in 2023. Conclusions and Suggestions: In providing education to pregnant women, midwives can collaborate with other health teams, in providing health education it can be added by using the WhatsApp application in the form of groups of pregnant women so that it is easy to provide health information for pregnant women in groups.